YAMA İLE TAMİR EDİLMİŞ ÇATLAK İÇEREN KOMPOZİTLERİN DARBE DAVRANIŞLARININ İNCELENMESİ - YEŞİL, AHMET (Fırat Üniveristesi, 2025)
Bu çalışmada, çatlak ve dairesel delik içeren kompozit plakaların düşük hızlı darbe davranışı deneysel ve sayısal olarak incelenmiş ve harici yama ile onarımının darbe dayanımı üzerindeki etkinliği değerlendirilmiştir. Çalışma kapsamında, yama ile onarılmış ve onarılmamış numuneler; hasar konumu delik çapı, darbe yönü ve darbe enerjisi parametreleri dikkate alınarak hazırlanmış ve düşük hızlı darbe deneylerine tabi tutulmuştur. Deneysel sonuçlar kuvvet-zaman, kuvvet-deplasman ve enerji-zaman eğrileri üzerinden karşılaştırmalı olarak analiz edilmiştir. Elde edilen bulgular, harici yama onarımının delik etrafındaki çatlak nedeniyle zayıflayan bölgede yük aktarım sürekliliğini yeniden sağlayarak darbe dayanımını belirgin biçimde arttırdığını göstermiştir. Yama ile onarılmış delikli plakaların maksimum temas kuvvetinin, yamasız plakaya göre %40-50 oranında arttığı tespit edilmiştir. Hasar bölgesinin darbe merkezinden konumsal değişimler; maksimum deplasman ve soğurulan enerjiyi %15-20 aralığında değiştirmiştir. Darbe yönü incelendiğinde, arkadan darbe alan numunelerde hasar gelişiminin daha ani ve düzensiz olduğu belirlenmiştir.

In this study, the low-velocity impact behavior of cracked composite plates repaired using bonded patches was investigated through experimental and numerical approaches, and the effectiveness of external patch repair on impact resistance was evaluated. Within the scope of the study, both patched and unpatched specimens containing cracks and circular holes were manufactured, and low-velocity impact tests were carried out by considering key parameters such as crack length, hole diameter, impact direction, and impact energy. Experimental results were comparatively analyzed based on force–time, force–displacement, and energy–time response curves. The findings demonstrate that external patch repair significantly enhances load transfer around the damaged region by bridging the crack formed around the hole, thereby improving the impact resistance of the composite plates. It was determined that the maximum contact force of patched specimens increased by approximately 40–50% compared to unpatched plates, indicating a substantial recovery in impact load-carrying capacity due to the repair process. Additionally, damage distribution following impact was observed to shift away from the impact center in patched specimens, while the maximum displacement and absorbed energy varied within the range of 15–20%, depending on crack length and impact conditions. The influence of impact direction was also examined, revealing that specimens subjected to rear-face impact exhibited more abrupt and irregular damage evolution compared to front-face impact cases. Overall, the results confirm that bonded patch repair is an effective method for restoring and improving the low-velocity impact performance of cracked composite plates. The combined experimental and numerical findings provide valuable insight into the damage mechanisms of repaired composites and contribute to a better understanding of the effects of geometric and loading parameters on impact behavior.
Examination of impact behavior of composites containing crack repaired by patching
Keywords: Makine Mühendisliği